Alteration of dopamine, homovanillic acid (HVA) with interleukine-1Î² (IL-1Î²) and tumor necrosis factor-Î± (TNF-Î±) in cerebral palsy (Biodiversitas Journal of Biological Diversity, 2016)
Now, diagnosis of cerebral palsy base only on clinical finding without involve the alteration of the neurochemistry cause by cerebral hypoxic, although cerebral palsy is a syndrome cause by cerebral hypoxic; so, the accuracy diagnosis of this disease is very low. The aim of this study is to know the alteration of neurochemistry in cerebral palsy, especially the dopamine, homovanillic acid (HVA), interleukine-1Î² (IL-1Î²) and tumor necrosis factor-Î± (TNF-Î±). So, in the future, diagnosis of this disease not only base on clinical finding as above, but must be combine with alteration of the neurochemistry. This study is conducted by observational method as cross-sectional study. Material of this study is venous blood; take by periphery venous blood vessels on median cubital vein at the upper arm. Dopamine analysis by RIA and homovanillic acid (HVA) by HPLC while Interleukine-1Î² (IL-1Î²) and tumor necrosis factor-Î± (TNF-Î±) analysis by ELISA. The result of this study show the alteration of dopamine, homovanillic acid (HVA), interleukine-1Î² (IL-1Î²) and tumor necrosis factor-Î± (TNF-Î±), in the spastic and dyskinetic type of cerebral palsy.Â Key words: IL-1Î², TNF-Î±, dopamine, HVA, cerebral palsy